Structure of the wedge-top and foredeep of the Magallanes-Malvinas basins between 62° W and 67° W (SW Atlantic Ocean). (August 2019) - Ormazabal, Juan Pablo; Tassone, Alejandro; Esteban, Federico; Isola, José; Cayo, Lubin Eric; Lozano, Jorge; Menichetti, Marco; Lodolo, Emanuele
Abstract: This work analyzes the geometry and geodynamic development of the offshore sector (between 62° W and 67° W) of the south Magallanes and Malvinas basins wedge-top and foredeep, and associated orogenic wedge. It is based on the interpretation of more than 20, 000 km of multichannel seismic profiles, along with bathymetric data. The fold-and-thrust belt front was mapped, and three structural domains were distinguished: western, transitional and eastern. A stepped foredeep characterizes the western domain with flower-structures that affect the basement, and by an intense erosion in the Miocene deposits. Towards the transitional domain, the erosion is less evident, and the wedge-top is more developed. This configuration is associated with the syn-deformational deposition and the generation of thrusts within an acoustically chaotic body in the transitional and eastern domains, deposited by processes of mass removal in the Oligocene. During the Oligocene/Miocene, the area was affected by compression/transpression, which generated an incipient tectonic inversion of the basement extensional faults, with the formation of anticlines associated with piggy-back basins in the wedge-top. The differences observed between the western and eastern domains would be related to the differential movement between the crustal blocks of Tierra del Fuego and Burdwood Bank, respectively, against the South American shelf since the Oligocene. Highlights: We present a study based on 2d seismic and well data in offshore Magallanes and Malvinas basins. The main seismic units and structures were studied and mapped in the wedge top and foredeep. Three domains were defined (western, central and eastern) from the differences through the studied area. The differences between domains were assigned to the differential movement between Tierra del Fuego and Burdwood Bank.